Arthroscopic Resection of a Large Osteochondroma of the Femoral Neck Overlying the Neurovascular Bundle: A Case Report - Krueger, Van Schaumburg; Dove, James Houston; Cohen, Eric; Tabaddor, Ramin (The Journal of Hip Surgery, 2022)
Only a few case reports have described the treatment of proximal femoral osteochondromas with excision using hip arthroscopy. We present the case of a 21-year-old male who presented with hip pain caused by an osteochondroma about the right femoral neck. Imaging obtained revealed a lesion that measured 4.4 × 3.2 × 5 cm abutting the neurovascular bundle along its anterior margin. After failed conservative measures, the patient underwent successful arthroscopic resection using two portals. This is the first case report presenting an arthroscopic resection of an osteochondroma located about the femoral neck adjacent to the neurovascular bundle.
Keywords: Proximal femur; Hip; Arthroscopy; Osteochondroma